2014
DOI: 10.14800/rci.291
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protease-Activated Receptors 2 (PAR2) in Ocular Infections and Inflammation

Abstract: Protease-activated receptors (PARs) belong to a unique family of G protein-coupled receptors (GPCRs) that are cleaved at an activation site within the N-terminal exodomain by a variety of proteinases, essentially of the serine (Ser) proteinase family. After cleavage, the new N-terminal sequence functions as a tethered ligand, which binds intramolecularly to activate the receptor and initiate signaling. Cell signals induced through the activation of PARs appear to play a significant role in innate and adoptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The involvement of PARs in DED was never mentioned until recently when Joossen et al described a significant increase in PAR-2 expression on the corneal tissue of untreated dry eye rats [ 38 ]. Several studies indicate the expression of PAR-1 and PAR-2 in HCE [ 76 , 102 , 103 ]. Lang et al also demonstrated that a specific activation of PAR-2 by trypsin and thrombin increased the production of the proinflammatory cytokines IL-6, IL-8, and TNF-α by HCE [ 102 ].…”
Section: Protease-activated Receptors and Dry Eye Diseasementioning
confidence: 99%
“…The involvement of PARs in DED was never mentioned until recently when Joossen et al described a significant increase in PAR-2 expression on the corneal tissue of untreated dry eye rats [ 38 ]. Several studies indicate the expression of PAR-1 and PAR-2 in HCE [ 76 , 102 , 103 ]. Lang et al also demonstrated that a specific activation of PAR-2 by trypsin and thrombin increased the production of the proinflammatory cytokines IL-6, IL-8, and TNF-α by HCE [ 102 ].…”
Section: Protease-activated Receptors and Dry Eye Diseasementioning
confidence: 99%